Interfaith Marriage in the Indonesian Legal System: An Analysis of Supreme Court Decision No. 1400 K/Pdt/1986 and Its Relevance to European Practice (A legal study of how the Indonesian Supreme Court handles interfaith marriage and a comparison with regul - Halim, Abdul; Ramadhan, Rizqi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
This article discusses the Supreme Court Decision No. 1400 K/Pdt/1986, which permits the registration of interfaith marriages in Indonesia as a response to the legal gap in the Marriage Law. Using a normative approach, a statute approach, and a comparative approach, this study finds that the Indonesian legal system emphasizes religious legitimacy before marriage registration is carried out. In contrast, the legal systems in the Netherlands and Turkey base marriage validity primarily on civil registration. Based on these findings, the study recommends adopting a European-style civil registration system to ensure legal certainty while respecting religious diversity in Indonesia.